The Role of Purchase Intention in Mediating the Influence of Price and Product Quality on Consumer Purchasing Decisions of Kopi Lingkar Malang - Ulum, Fahrul (International Journal of Economics, Business and Innovation Research, 2024)
Coffee shops have become a popular gathering place in the community. The coffee industry in Indonesia is experiencing rapid growth. Competition is also getting tighter. This study aims to examine and analyze the role of purchase intention in mediating the influence of price and product quality on purchasing decisions of consumers at Kopi Lingkar Malang. Kopi Lingkar Malang is one of the coffee shops located in Malang City. The research data used is primary data, obtained through distributing questionnaires to samples. The sample in this study consisted of 80 respondents. The type of research conducted in this study is explanatory research with a quantitative approach. The data gathering instrument used in this study is a questionnaire. The data analysis method used in this study is Partial Least Squares (PLS). The results obtained from this study conclude that the price variable does not affect purchase intention and purchasing decisions of consumers at Kopi Lingkar Malang. Product quality and purchase intention influence purchasing decisions. Product quality also influences consumer purchase intention. Furthermore, the price variable in this study did not influence purchasing decisions among consumers at Kopi Lingkar Malang, mediated by purchase intention. Furthermore, product quality in this study influenced consumer purchase decisions, mediated by purchase intention.